Scoliosis in a Patient With Gilbert Syndrome: A Case Report and Review of the Literature. Issue 47 (November 2015) - Li, Zheng; Shen, Jianxiong; Liang, Jinqian
Abstract : Abstract: Gilbert syndrome (GS) is mainly characterized by intermittent unconjugated hyperbilirubinemia in the absence of hepatocellular disease or hemolysis. Little data are available on operative outcomes in GS patients with spinal deformity surgery. This study has presented a case of GS occurring in the patient with scoliosis. The patient was a 30-year-old female with scoliosis and GS. She was taken a correction form Thoracic 2 to Lumbar 1) levels by using the USS-II spinal system. At 2 years follow-up, the patient was well balanced and pain free. Plain radiographs demonstrated spine solid fusion without correction loss. Although complex scoliosis surgery can be performed safely in these patients with GS, careful perioperative managements including liver function and coagulation function are required.